Metta Analisis Pengaruh Industri Manufaktur dan Industri Pertanian Terhadap Pertumbuhan Ekonomi - Rusmiati Rusmiati; Maulaya Arinal Haq; Levis Saputri (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The process of long-term improvement in the economic condition of a country to a better state over a certain period is called economic growth.When the level of economic activity is higher than that achieved in previous periods, the economy of a country is said to be experiencing growth.The purpose of this research is to determine the extent to which the manufacturing industry and the agricultural industry influence Indonesia's growth.This type of study is a qualitative study that uses the literature review method.This method is very suitable and relevant for analyzing the influence of the manufacturing industry and the agricultural industry.The results show that the manufacturing and agricultural sectors have a complex influence on Indonesia's economic growth.By becoming a leading sector, manufacturing can drive economic growth by creating more jobs and boosting other sectors such as trade and services.Foreign direct investment (FDI), bank credit, and the number of business units in certain sectors influence the development of the manufacturing sector.